EFFICACY AND SAFETY OF SIMVASTATIN IN RHEUMATOID ARTHRITIS: AN OPEN-LABEL, CONTROLLED STUDY - I. V. Shirinsky; O. I. Zheltova; V. S. Shirinsky; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. Recently discovered immune–modulating and anti-inflammatory properties of statins have resulted in application of these drugs for treatment of autoimmune disorders. There are few studies investigating therapeutic potential of simvastatin in rheumatoid arthritis (RA). In present study, we investigated efficacy and safety of simvastatin in active RA patients treated with conventional disease-modifying antirheumatic drugs (DMARDs). Thirty-three patients were enrolled into an open-label, controlled study. The patients received treatment with 40 mg of simvastatin daily for 12 weeks. A group of historical controls consisted of nine patients taking placebo combined with disease-modifying therapy. No differences in demographic characteristics and disease activity were observed between the two groups. By the end of therapy (12 weeks), simvastatin-treated patients exhibited a significant reduction in disease activity scores with 28-joint counts (DAS28), and according to physician’s assessment of disease, as compared with control group. The estimate of trea tment effect (DAS28 scores) was 0.76 (95% confidence interval 0.01-1.5), thus corresponding to moderate decrease in disease activity. In conclusion, combination therapy with simvastatin and conventional DMARDs results into decreased RA activity. However, additional studies are required in order to specify exact role of simvastatin in RA treatment. (Med. Immunol., vol. 10, N 4-5, pp 477-482).